Spatial data modelling for 3D GIS - Abdul Rahman, Alias (Springer Berlin Heidelberg, 2007)
This book is based on research works done by the authors at the University of Glasgow, Scotland, United Kingdom and the International Institute for GeoInformation Science and Earth Observation (ITC), The Netherlands in 2000 and 1996 respectively. We were motivated to write the book when we began a joint research work in 1992 for our postgraduate theses on Digital Terrain Modelling (DTM) data structuring and eventually DTM soft- ware development based on triangular irregular network (TIN) data structure. We realized then that many aspects needed to be addressed especially if an advanced geoinformation system (GIS) such as 3D GIS system was to be realized. Research in 3D GIS is getting growing in interest and this has really motivated us to do more experiments in the 3D domain. One of the most current interesting issues is spatial data modelling for 3D GIS.